PERANCANGAN VIDEO PROMOSI MILKINDO SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Anam, Syafiul; Martono, Siswo; Prasetya, Ardian Jaya (Jurnal Art Nouveau, 2018)
The problem in this final project is how to design Milkindo promotion media as an effort to increase Brand Awareness. Milkindo is basically a dairy cow milk company located in Tegalsari village, Kepanjen, Malang which follows the program from the government of education to the village community and then Milkindo participate in the program and develop the education to the community early but for Milkindo promotion media only rely on social media Instagram, therefore it takes a suitable media campaign to improve Milkindo Brand Awareness.